STUDY ON THE LOW-FIELD CHARGE-TRAPPING PHENOMENA IN THE SILICON-NITRIDE INP STRUCTURE - KIM, CH; KWON, SD; CHOE, BD; HAN, IK; LEE, JI; KANG, KN; HER, J; LIM, H (KOREAN PHYSICAL SOC, 1993)
The time dependence of the low-field charge-trapping behavior in silicon-nitride/InP metal-insulator-semiconductor structures was investigated by the constant-capacitance technique and C-V measurement. Silicon-nitride films were formed by a conventional plasma-enhanced chemical-vapor-deposition technique. The main traps were identified as silicon dangling bonds for all samples. The rate-limiting process of the charge trapping behavior at room temperature was found to be direct tunneling or hopping between traps depending on their density. The minimum trap density for hopping conduction was estimated to be about 1 X 10(19) cm-3. It was also found that a deficiency of phosphorus at the interface might induce net negative fixed charges in PECVD-grown silicon-nitride/InP MIS structures.
Keywords: ELECTRICAL HYSTERESIS; DEEP TRAP; STATES; INSTABILITIES; CAPACITORS; INTERFACE; DEFECTS